Targeting Nonsmokers to Help Smokers Quit: Features of a Large-scale Intervention - Gary J Tedeschi; Leslie S Zoref; Sharon E Cummins; Shu-Hong Zhu (SAGE Publishing, 2020)
Smoking continues to be a major public health problem, despite a substantial decline in prevalence rates over the last decades. Quit smoking interventions typically target smokers, whether through individual or group treatment or through broader public health campaigns. Yet, nonsmokers represent a vast and largely untapped resource to help smokers quit. This article describes an innovative approach that targeted nonsmokers through a media-style campaign with repeated reminders about smoking cessation. We tested the nonsmoker intervention in a large randomized trial and showed it to be effective in helping smokers quit. Components of the intervention included repeated mailings with relevant cessation messages over a 10-week period, 2 brief check-in telephone calls, and access to a study Web site. In this article, we discuss details of the intervention development, content, and implementation.